2020
DOI: 10.1177/0954406220939598
|View full text |Cite
|
Sign up to set email alerts
|

An observation of the evolution of equilibrium stress on poly(lactic acid) and poly(lactic acid)/hydroxyapatite nanocomposites

Abstract: Relaxation behavior provides specific information that indicates stress development with elapsed time for the determination of material characterization and constituting of material modeling. In addition, anomalous relaxation behavior of polymeric materials enables experimental analysis of some theoretical variables in constitutive equation. Equilibrium stress is one of the most prevailing variables in material modeling and it is generally considered as unmeasurable. In this study, evolution of equili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…Chacon et al presented similar effects of build orientation, feed rate, and layer thickness on tensile and three‐point bending properties of PLA fabricated by FDM 24 . Dusunceli studied tensile relaxation on PLA and PLA/hydroxyapatite (HA) and found that both strain rate and temperature had great effects on the mechanical responses of the materials 26 . Our previous studies employed a three‐point bending test to investigate the flexural strength of PLA and PLA/HA under different degradation conditions 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Chacon et al presented similar effects of build orientation, feed rate, and layer thickness on tensile and three‐point bending properties of PLA fabricated by FDM 24 . Dusunceli studied tensile relaxation on PLA and PLA/hydroxyapatite (HA) and found that both strain rate and temperature had great effects on the mechanical responses of the materials 26 . Our previous studies employed a three‐point bending test to investigate the flexural strength of PLA and PLA/HA under different degradation conditions 27,28 .…”
Section: Introductionmentioning
confidence: 99%